1997
DOI: 10.1021/jp963070u
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of 1,1,2-Trichlorotrifluoroethane Initiated by TiO2 Particles

Abstract: Reductive dehalogenation of 1,1,2-trichlorotrifluoroethane (CFC 113) takes place upon illumination of air-free suspensions of TiO2 particles containing formate ions. Chloride ions and 1,2-dichlorotrifluoroethane (HCFC 123a) are the main reaction products. Reaction rates increase with increasing concentration of CFC even beyond the solubility limit of the Freon in water. Evidence is presented that a chain transformation of the Freon takes place in formate solutions. The results are explained assuming that reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 40 publications
8
28
0
Order By: Relevance
“…Included in the inset is a plot showing that the ϕ­(Cl – ) variation was nearly linear with I 0 –1/2 . Similar dependencies were noticed for the photoreductions of CCl 4 , CCl 3 F, and CCl 2 FCClF 2 ,,, and are typical of chain transformations involving radical–radical termination reactions . As for CFC 113, the CHCl 3 dehalogenation was characterized by low quantum efficiencies at all photon fluxes.…”
Section: Resultssupporting
confidence: 75%
“…Included in the inset is a plot showing that the ϕ­(Cl – ) variation was nearly linear with I 0 –1/2 . Similar dependencies were noticed for the photoreductions of CCl 4 , CCl 3 F, and CCl 2 FCClF 2 ,,, and are typical of chain transformations involving radical–radical termination reactions . As for CFC 113, the CHCl 3 dehalogenation was characterized by low quantum efficiencies at all photon fluxes.…”
Section: Resultssupporting
confidence: 75%
“…Tan et al [1179][1180][1181][1182] have shown that the nature of the sacrificial electron donor is important, with formate showing the most promise. Other photoreduction systems of interest include iodine/triiodide [422,495] and a variety of halocarbons photoreduced through radical chain reactions [1001,[1183][1184][1185].…”
Section: Nitrogen-containing Moleculesmentioning
confidence: 99%
“…Weaver [89] showed that reductive dehalogenation of trichlorotrifluoroethane (CFC-113), took place upon illumination of air-free suspensions of TiO 2 particles containing formate ions.…”
Section: Cfc-113mentioning
confidence: 99%